THE ROLE OF VIRTUAL LABS IN PHYSICS TEACHING - Iskandaryan, A. (SUSh Scientific Proceedings, 2025)
This article examines the application of virtual laboratories in physics education, highlighting their role in enhancing teaching effectiveness. Based on platforms such as phet.colorado.edu, efizika.ru, and esource.armedu.am, it explores the capabilities of digital tools, their impact on the educational process, and ways to integrate virtual and traditional labs. Concrete examples of lessons incorporating virtual experiments are presented, emphasizing opportunities for personalized learning and fostering independent work. The studied approaches demonstrate that virtual laboratories promote the development of research skills, enable interactive learning, and complement traditional lab work. The article underscores that such digital resources can stimulate students’ interest in physics, cultivate their critical and analytical thinking, and facilitate the accessible presentation of complex phenomena. Additionally, virtual labs contribute to saving time and resources, which is particularly relevant for schools with limited technical and material capabilities. The article highlights the role of virtual laboratories in distance learning, where they allow experimental work to be conducted even when students and teachers are not physically present in the same classroom. It also addresses the necessity of preparing educators to effectively utilize such platforms. This paper is intended for physics teachers as well as professionals interested in educational technologies and methodologies